The Influence of Cultural Backgrounds on Team Dynamics and Decision Making in Multicultural Environments - Xie, Zhongyu (Transactions on Economics, Business and Management Research, 2024)
With the deepening development of globalization, cross-cultural communication is becoming increasingly frequent, and the role of multicultural teams in enterprises, education, scientific research, and other fields is becoming increasingly prominent. However, while multicultural teams bring innovation and competitive advantages, they also face challenges such as cultural conflicts and communication barriers. This study aims to explore the strategies and challenges of multicultural teams in cross-cultural communication, as well as how to improve team effectiveness through effective management. Using case analysis method, multiple multinational corporations were selected as research objects, and data was collected through literature review and other methods to analyze the operational mode and management strategy of multicultural teams. Research has found that cultural sensitivity training, cultivation of cross-cultural communication skills, establishment of shared values, and flexible management styles are key strategies for enhancing the effectiveness of multicultural teams. Meanwhile, cultural conflicts and communication barriers are the main challenges. Effective management of multicultural teams is crucial for enhancing team effectiveness. Enterprises should attach importance to cross-cultural training, strengthen communication and understanding among team members, in order to overcome the challenges brought by cultural differences and achieve collaborative development of the team.